Constructing an Islamic-Based Medical Worldview - Ibrahim, Mohamad Zaki; Hanapi, Mohd Shukri (Journal of Techno-Social, 2025)
While many muslim majority countries have launched initiatives such as Islamic input in medical curriculum, Ibadah-Friendly Hospitals and Shariah-Compliant Hospitals to embed Islamic values in healthcare, modern medicine continues to be dominated by secular worldview. This paper argues that the integration of Islamic principles into medicine has largely been superficial because it is not founded upon an Islamic worldview (tasawwur). The result is worldview fragmentation, what may be called conceptual chaos between Islamic creeds and medical practice. This study constructs an Islamic-based medical worldview through qualitative research and document analysis. The framework reconstructs the foundations of medicine around seven key elements, that is Islamic creed (tauhidic), role (khilafah), knowledge, worship, ethics, God presence (Ihsan), and purpose. This study propose tasawwur as the foundation layer above existing hospital initiatives, forming a three-tier model that integrates worldview, regulation, and operation. This paper concludes that genuine Islamization of medicine must begin with worldview reconstruction rather than ethical or operational addition.